A Study on the Affected Children’s Coping Strategies and Psychological Adjustments Following a Natural Disaster in Sri Lanka - Samudra Kumari Senarath (TDMRC, Universitas Syiah Kuala, 2019)
Children who experience catastrophic disasters and events show a wide range of trauma reactions. In the absence of effective coping, for traumatic events may affect psychological development of children. The objectives of this study were to examine the tsunami affected the children and adolescents, efforts in coping strategies mobilized to manage with posttraumatic stress after seven years of the tsunami 2004, to assess the psychological adjustment and to examine changes in different coping styles after the psychological intervention. A quasi-experimental, two-group design with a pre-test and post-test was conducted to determine success of the intervention in children. Data were collected from 80 children and adolescents being affected by the tsunami, with n=40 in the experimental group (EG) and n=40 in the control group (CG) using standardized test, Child Coping Questionnaire (CCQ). To facilitate psychological well-being, psychological intervention was implemented three months including twenty sessions. Pre-test results (prior to intervention) proved both groups of children had relationship between posttraumatic stress and coping strategies. Two ways ANOVA with three measurement times showed that EG children’s coping styles were decreased and changed the negative coping in contrast to the CG. The Amos’ model predictive analysis also showed EG children were not required efforts to cope with posttraumatic stress in compared to the CG. Problem-focused and support- seeking coping scales, long-term and stabilization effects were failed, this means both groups need more help in social support and to solve their problems. The findings suggested that psychological intervention need to be implemented in long-term for the both group children’s well-being.